Marketing Treatment in Madura Culture-Based Used Metal Business Based on Umer Chapra Perspective - Fuad, Maf Tuhul; Sutarso, Yudi (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Umer Chapra's thinking, as an Islamic economic scholar, adds an ethical and justice dimension to the study of UD. Sumber Logam in the context of Madurese culture. Chapra emphasizes the importance of Islamic economic principles that include distributive justice, social responsibility, and sustainability. The integration of Chapra's thoughts with UD's marketing strategy. Sumber Logam can create a holistic and sustainable approach so as to expand market share and strengthen relations or good relations between consumers and UD. Sumber Logam. The method used in this research is qualitative method. Data collection techniques in this study used observation, interviews and documentation. The results of this study indicate that UD Sumber Logam in the scrap metal business seeks to apply the principles of Islamic economics according to Umer Chapra, namely justice, transparency, and benefits for society, especially in the marketing aspect. Currently, businesses still rely on conventional methods, but are starting to switch to digital marketing through social media and modern advertisements that are honest and educative. The use of technology is also applied to improve efficiency and expand market reach, such as online catalogs and digital ordering services. Transparency is maintained with regular weighing controls and regular price updates for customers' trust and convenience.